Evidence of digenic inheritance in Alport syndrome. Issue 3 (9th January 2015) - Mencarelli, Maria Antonietta; Heidet, Laurence; Storey, Helen; van Geel, Michel; Knebelmann, Bertrand; Fallerini, Chiara; Miglietti, Nunzia; Antonucci, Maria Fatima; Cetta, Francesco; Sayer, John A; van den Wijngaard, Arthur; Yau, Shu; et al.
Abstract : Background: Alport syndrome is a clinically heterogeneous, progressive nephropathy caused by mutations in collagen IV genes, namely COL4A3 and COL4A4 on chromosome 2 and COL4A5 on chromosome X. The wide phenotypic variability and the presence of incomplete penetrance suggest that a simple Mendelian model cannot completely explain the genetic control of this disease. Therefore, we explored the possibility that Alport syndrome is under digenic control. Methods: Using massively parallel sequencing, we identified 11 patients who had pathogenic mutations in two collagen IV genes. For each proband, we ascertained the presence of the same mutations in up to 12 members of the extended family for a total of 56 persons studied. Results: Overall, 23 mutations were found. Individuals with two pathogenic mutations in different genes had a mean age of renal function deterioration intermediate with respect to the autosomal-dominant form and the autosomal-recessive one, in line with molecule stoichiometry of the disruption of the type IV collagen triple helix. Conclusions: Segregation analysis indicated three possible digenic segregation models: (i) autosomal inheritance with mutations on different chromosomes, resembling recessive inheritance (five families); (ii) autosomal inheritance with mutations on the same chromosome resembling dominant inheritance (two families) and (iii) unlinked autosomal and X-linked inheritance having a peculiar segregation (four families). This pedigree analysis provides evidence for digenic inheritance of Alport syndrome. Clinical geneticists and nephrologists should be aware of this possibility in order to more accurately assess inheritance probabilities, predict prognosis and identify other family members at risk.